Omega-3 Fatty Acids: Anti-Arrhythmic, Pro-Arrhythmic, or Both? - von Schacky, Clemens (Frontiers in Physiology, 2012)
Abstract This review focuses on developments after 2008, when the topic was last reviewed by the author. Pertinent publications were found by medline searches and in the author’s personal data base. Prevention of atrial fibrillation (AF) was investigated in a number of trials, sparked by one positive report on the effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), considerations of upstream therapy, and data from electrophysiologic laboratories. If EPA+DHA prevent postoperative AF, the effect is probably smaller than initially expected. The same is probably true for maintenance of sinus rhythm after cardioversion and for new-onset AF. Larger trials are currently ongoing. Prevention of ventricular arrhythmias was studied in carriers of an implanted cardioverter-defibrillator, with no clear results. This might have been due to a broad definition of the primary endpoint, including any ventricular arrhythmia and any action of the device. Epidemiologic studies support the contention that high levels of EPA+DHA prevent sudden cardiac death (SCD). However, since SCD is a rare occurrence, it is difficult to conduct an adequately powered trial. In patients with congestive heart failure, EPA+DHA reduced total mortality and rehospitalizations, but not SCD or presumed arrhythmic death. Of three trials in patients after a myocardial infarction, two were inadequately powered, and in one, the dose might have been too low. Taken together, while epidemiologic studies support an inverse relation between EPA+DHA and occurrence of SCD or arrhythmic death, demonstrating this effect in intervention trials remained elusive so far. A pro-arrhythmic effect of EPA+DHA has not been seen in intervention studies, and epidemiologic studies also rather argue against such an effect. A different, and probably more productive, perspective is provided by a standardized analytical assessment of a person’s status in EPA+DHA by use of the Omega-3 Index, EPA+DHA in red cell fat